Allergy - Holgate, S. T.; ClinicalKey eBooks (Edinburgh : Elsevier Saunders, 2012)
The new edition of Allergy, by Drs. Stephen Holgate, Martin Church, David Broide, and Fernando Martinez, uses an enhanced clinical focus to provide the clear, accessible guidance you need to treat allergy patients. A more consistent format throughout features new differential diagnosis and treatment algorithms, updated therapeutic drug information in each chapter, and additional coverage of pediatric allergies. With current discussions of asthma, allergens, pollutants, drug treatment, and more, as well as access to the full text and illustrations online at www.expertconsult.com, this comprehensive resource is ideal for any non-specialist who treats patients with allergies. Prescribe appropriate therapies and effectively manage patients' allergies using detailed treatment protocols. Identify allergic conditions quickly and easily with algorithms that provide at-a-glance assistance. Explore topics in greater detail using extensive references to key literature.
Introduction to mechanisms of allergic disease -- Genetic basis of allergy and asthma -- Early life origins of allergy and asthma -- Epidemiology of allergy and asthma -- Allergens and air pollutants -- Principles of allergy diagnosis -- Principles of pharmacotherapy -- Allergen-specific immunotherapy -- Asthma -- Allergic rhinitis and rhinosinusitis -- Allergic conjunctivitis -- Urticaria and angioedema without wheals -- Atopic dermatitis and allergic contact dermatitis -- Food allergy and gastrointestinal syndromes -- Occupational allergy -- Drug hypersensitivity -- Anaphylaxis -- Paedatric allergy and asthma -- Eosinophilia: clinical manifestations and therapeutic options -- Systemic mastocytosis.
Print version record.
Includes bibliographical references and index.
Previous edition: Edinburgh: Elsevier Mosby, 2006.
Elsevier
Elsevier
Keywords: Allergy; Hypersensitivity; HEALTH & FITNESS -- Allergies; HEALTH & FITNESS -- Diseases -- Immune System; MEDICAL -- Immunology; Allergy; Electronic books